Fluorinated POSS‐Star Polymers for 19F MRI. Issue 20 (6th May 2016) - Wang, Kewei; Peng, Hui; Thurecht, Kristofer J.; Whittaker, Andrew K.
Abstract : Star polymers with a polyhedral oligomeric silsesquioxanes (POSS) core and eight partly fluorinated arms have been synthesized by reversible addition–fragmentation chain transfer polymerization. A macroCTA having eight chain transfer agent (CTA) molecules attached to a POSS core is prepared and used for the synthesis of star polymers by the R‐group approach. The arms are composed of statistical copolymers of 2, 2, 2‐trifluoroethyl acrylate and poly(ethylene glycol) methyl ether acrylate. The polymerization kinetics are studied, and yield of star polymer is optimized. Star polymers having different arm lengths are prepared and characterized. The star polymers exhibit a single 19 F resonance in 19 F nuclear magnetic resonance spectra in aqueous solution, and the T 2 relaxation time increases with arm length. The relaxation properties and the fluorine content are consistent with these polymers being effective 19 F magnetic resonance imaging (MRI) agents. This work indicates that these POSS‐star polymers have potential as theranostic agents for 19 F MRI and drug delivery. Abstract : Novel hybrid star polymers with a polyhedral oligomeric silsesquioxane core and eight partly fluorinated copolymer arms are synthesized through R‐group approach by reversible addition–fragmentation chain transfer (RAFT) polymerization. The 19 F magnetic resonance imaging (MRI) capability is preliminarily confirmed by a single and strong 19 F resonance in 19 F nuclear magnetic resonance (NMR), and the imaging intensity is also calculated for a spin‐echo pulse sequence.